MgO NPs catalyzed the synthesis of novel pyridin-3-yl-pyrimidin-2-yl-aminophenyl-amide derivatives and evaluation of pharmacokinetic profiles and biological activity - Gani, Ibtihal Haitham; Al-Obaidi, Zaid (Frontiers in Materials, 2023)
In this study, new pyridin-3-yl-pyrimidin-2-yl-aminophenyl-amide derivatives with two methods, using of trimethylamine as classical method and the using of magnesium oxide nanoparticles were synthesized. Biological activity of them such as inhibitors of receptor tyrosine kinase, pharmacokinetics profiles, anticancer activity against lung cancer, antibacterial and antifungal activity against specialized aquatic bacterial species, gram positive and gram negative species and fungal species and antioxidant activity of them were evaluated. The structure of synthetic derivatives by using FTIR, 1H-NMR,13C-NMR spectrums an elemental analysis were confirmed. As a result, these compounds possess more cytotoxic activity than the reference drug (i.e., Imatinib). Furthermore, compound IIB gives ten folds fewer IC50 (0.229 μM) compared with imatinib (2.479 μM) when tested against (A549) lung cancer cell lines employing the MTT assay. In the investigation of antibacterial and antifungal activities, Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Minimum Fungicidal Concentration (MFC) parameters were evaluated and derivative IIC showed the highest activity (MIC 16-128 μg/mL), which can be attributed to its structure. In addition, the antibacterial and antifungal properties of were higher than some drugs. In antioxidant property of the derivatives that were was studied by the DPPH (2,2-diphenylpicrylhydrazyl) method, IC50 value were evaluated and results close to ascorbic acid (4.45-4.83 μg/ml).